PTSL Policy Analysis from the Perspective of Legal Certainty, Justice and Benefits: Challenges and Opportunities - Srinadi, Ni Gusti Ayu Made; Wijaya, I Ketut Kasta Arya; Sukadana, I Ketut (IHSA Institute, 2024)
Legal certainty, fairness, and community benefits are the goals of Indonesia's Complete Systematic Land Registration Program (PTSL), which seeks to streamline and simplify the land registration process. The purpose of this study is to examine the PTSL policy and its execution in order to draw conclusions about the program's strengths and weaknesses in terms of its ability to provide legal certainty, fairness, and advantages. This study delves into the effects of PTSL on several parts of Indonesian agricultural legislation using a qualitative method with normative analysis. Although PTSL has improved access to land rights and legal clarity, the study found that indigenous peoples' rights, conflict resolution, and equitable benefit sharing remain major obstacles. In order to maximize the effectiveness of PTSL implementation, this study suggests three main strategies: enhancing regulatory frameworks, empowering communities, and strengthening the ability to implement